The History of Intimacy - Baderoon, Gabeba (WritingThreeSixty, 2018)
I. You remember it because itâ€™s a wound. A cut, twenty cuts, the name for the canings on the palm, on the knuckles, on the buttocks, a finely graded order of pain that we who should not exist were assigned for our failures. II. You keep you white, nuh, Mike shouts in 1987 across the heads of students sitting on Jameson Steps and the sudden white silence shows we are no longer in uniform in the quad at Livingstone High, teasing hey, why did you look through me as though I donâ€™t exist. And this slipping from being we called keeping you white, but saying it out loud reveals how we have learned to measure our existence. III. In the video store after Iâ€™ve ordered a film, my cousin elbows me, Why you putting on? Putting on. Transitive verb. Putting on what? Putting on skin, putting on not nothingness. IV. When the Group Areas Act is abolished, my mother aches to go back to the street she was removed from and it is we, grown attached to the scar we call home, who say, No, we donâ€™t want to live in a white area, this time ceding it ourselves. V. In 1988 at Crawford train station, my brother and I find a blue plank hand-painted in yellow letters: â€œNon-Whites Onlyâ€ on one side â€œWhites Onlyâ€ on the other thrown away by the fence next to the tracks. Picking it up, we see the two sides of the sign lay back to back, each half resting against its opposite, intimate and inverse but unknown to each other. We knew this was history someone had made by hand then hidden and tried to forget. We bring it home and come across it sometimes in a corner when weâ€™re looking for something else.